2018
DOI: 10.20546/ijcmas.2018.711.375
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Anticancer Potential of Natural Drugs: Hispolon and Limonene

Abstract: In this context, natural products derived from the biological sources have emerged as the first choice of researchers. Accordingly, several plant-/fungal-/bacterial-derived natural products are in diff erent stages of evaluation as new therapeutic agents (Veeresham, 2012 andBernardini et al., 2017). There has been also a growing interest among the researchers for exploring synthetic derivatives of natural products as a novel class of drugs with multiple activities and target specificity. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The anticancer properties of the major components in S. verbenaca (carvacrol, limonene, and thymol) have also been reported recently [ 80 82 ]. Thymol has been shown to have anticancer properties via a variety of mechanisms, including inducing severe DNA damage, including the production of reactive oxygen species (ROS) and subsequent increase in oxidative stress and/or mitochondrial dysfunction, or via the nuclear factor of activated T cell (NFAT-2) route [ 81 ].…”
Section: Methodsmentioning
confidence: 93%
“…The anticancer properties of the major components in S. verbenaca (carvacrol, limonene, and thymol) have also been reported recently [ 80 82 ]. Thymol has been shown to have anticancer properties via a variety of mechanisms, including inducing severe DNA damage, including the production of reactive oxygen species (ROS) and subsequent increase in oxidative stress and/or mitochondrial dysfunction, or via the nuclear factor of activated T cell (NFAT-2) route [ 81 ].…”
Section: Methodsmentioning
confidence: 93%
“…Numerous studies have been published on the anticancer activity of the main compounds of oregano EOs such as limonene, carvacrol, and thymol [62][63][64]. Islam et al [63] determined that the mechanism of action of thymol in a cancer cell caused severe DNA damage through several mechanisms (e.g., ROS induction and subsequent increase in oxidative stress and/or mitochondrial dysfunction or nuclear factor of activated T-cells (NFAT-2) pathway), which eventually upregulates Bax/Bcl-2 protein expression and results in the cytochrome-(cyto-) c release from the mitochondria (intrinsic pathway).…”
Section: Biological Mechanism Insights Into O Elongatum Main Compoundsmentioning
confidence: 99%
“…Hispolon belongs to a polyphenol compound, which was found in several types of mushrooms such as Inonotus hispidus , Phallus linteus , and Phellinus igniarius 18 . To date, hispolon has been widely discovered to have the activities of anti‐virus, 18 anti‐oxidant, 19 anti‐inflammatory, 20 hepato‐protective, 21 and anticancer 22 . Huang et al have shown the apoptotic effect of hispolon by modulating ERK pathway on hepatocellular carcinoma cells 23 .…”
Section: Introductionmentioning
confidence: 99%